1999
DOI: 10.1590/s0001-37141999000300007
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of fine fluorite particles with Corynebacterium xerosis

Abstract: The treatment of fine particles dispersed in liquids is common in several industries and especially important in mineral processing. The efficiency of settling operations can be substantially increased by flocculation. The aim of this work was to study the flocculation of fine fluorite particles by the bacterium Corynebacterium xerosis. Flocculation tests, microelectrophoresis measurements and optical microscopy were used to evaluate flocculation. The results showed that C. xerosis cells adhere to the fluorite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The acidbase properties and ion exchange reactions on the fluorite surface were determined by Wu and Forsling (1995) while Haas et al (1999), Miller et al (2004), Fuerstenau and Bunge (2006) and Assemi et al (2006) investigated the influence of pH on zeta potential. They found that the maximum values of the fluorite zeta potential of ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acidbase properties and ion exchange reactions on the fluorite surface were determined by Wu and Forsling (1995) while Haas et al (1999), Miller et al (2004), Fuerstenau and Bunge (2006) and Assemi et al (2006) investigated the influence of pH on zeta potential. They found that the maximum values of the fluorite zeta potential of ca.…”
Section: Methodsmentioning
confidence: 99%
“…30 to over 200 ms (depending on surface roughness and the fluorite sample origin). Table 1 The TPC formation in respect to changes of pH and zeta potential of the fluorite (Sample A) and bubble interfaces According to (Haas et al, 1999;Miller et al, 2004;Assemi et al, 2006) the isoelectric point of fluorite was 9.0-10.5.…”
Section: Influence Of Ph On the Bubble Attachment To Fluorite Surfacementioning
confidence: 99%
“…Tanaka et al filtered six different bacterial strains (including E. coli ) under the same operating conditions (0.5 bar and around 10 4 CFU/mL) on PC track‐etched membranes (pore size, 0.4 µm) and found that E. coli was able to pass through the membrane even though its average pore size was smaller than the bacterium (2 × 1 µm 2 ). However, Corynebacterium xerosis with a similar size (1 µm) and shape as E. coli did not leak through. This may be due to the ability of some microorganisms to change shape, volume, and/or size physiologically as a result of mechanical stress and osmotic/transmembrane pressure applied on the cell .…”
Section: Filtration Efficiencymentioning
confidence: 99%
“…Microelectrophoresis measurements and optical microscopy testing are used to evaluate flocculation. Interesting work on flocculation of fine fluorite particles by the bacterium Corynebacterium xerosis has been reported by Haas et al (1999). The cells of C. xerosis adhere to the fluorite surfaces and promote the aggregation of the particles to achieve high quality flocks.…”
Section: Functional Properties Of Surfactant/emulsifiermentioning
confidence: 99%